Maturational and social factors contributing to relative age effects in school sports: Data from the London Youth Games - Reed, K. E.; Parry, D. A.; Sandercock, G. R. H. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Few studies have investigated whether relative age effects (RAEs) exist in school sport. None have sought to test the competing maturational and social-agent hypotheses proposed to explain the RAE. We aimed to determine the presence of RAEs in multiple school sports and examine the contribution of maturational and social factors in commonplace school sports. We analyzed birth dates of n=10645 competitors (11-18 years) in the 2013 London Youth Games annual inter-school multisport competition and calculated odds ratio (OR) for students competing based on their yearly birth quarter (Q1-Q4). Multivariate logistic regression was used to determine the relative contribution of constituent year (Grade) and relative age in netball and football which used multiyear age groupings. In girls, RAEs were present in the team sports including hockey, netball, rugby union, cricket and volleyball but not football. In boys, RAEs were stronger in common team sports (football, basketball cricket) as well as athletics and rowing. In netball and football teams with players from two constituent years, birth quarter better-predicted selection than did constituent year. Relatively older players (Q1) from lower constituent years were overrepresented compared with players from Q3 and Q4 of the upper constituent years. RAEs are present in the many sports commonplace in English schools. Selection of relatively older players ahead of chronologically older students born later in the selection year suggests social agents contribute to RAEs in school sports.